VIRTUAL REALITY ENVIRONMENT TO MONITOR WORKPLACE STRESS - Parman, Siti Nursyahirah (Universiti Teknologi PETRONAS, 2021)
Workplace stress is one of the mental health issues that get the attention in the community as it gives impact to everyday businesses. Since workplace stress give negative impact to the companies or organizations financially and socially, managements have put their effort in monitoring the stress amongst the employees by using psychologist services. Initially, the stress monitoring process will be done by using surveys and questionnaires. However, recently people are working on creating virtual environment of workplace stress to emulate the real world. This paper shows the workflow of creating an immersive virtual environment of an office replicating the real-world office environment acting as a medium to get the real-time results. The virtual environment is created in a game engine with the usage of assets available in it. Some sounds are included into the scene in order to create the sense of immersion in the virtual environment. Some stressful events are included in the project for example workloads, abundance of due dates, unpleasant workplace and noise.